Surgical Reduction of Tumour Bulk in Management of Abdominal Burkitt's Lymphoma. Issue 5914 (11th May 1974) - Magrath, I. T.; Lwanga, S.; Carswell, W.; Harrison, N.
Abstract : The results of a retrospective study of the value of reductive surgery in the treatment of abdominal Burkitt's lymphoma are reported. Nine patients had almost complete removal of the tumour, 16 had little over half of the tumour removed, and 43 underwent biopsy only. All patients subsequently received chemotherapy. There was a highly significant difference in the proportion of patients achieving a sustained durable remission (P > 0·0001) and a significant difference in survival (P > 0·05) between the group having almost complete removal and the partial resection group. Partial resection gave no advantage over no surgery. We believe that whenever possible complete removal of the abdominal tumour should be attempted regardless of the presence of extra-abdominal tumour; but unless at least 90% of the tumour can be removed there is no advantage in partial resection in terms of response to subsequent chemotherapy. In particular the removal of one of two involved ovaries can no longer be recommended. The implications of these results are related to cancer treatment strategy.